2013
DOI: 10.3171/2013.4.jns121546
|View full text |Cite
|
Sign up to set email alerts
|

Importance of awareness of the rhomboid lip in microvascular decompression surgery for hemifacial spasm

Abstract: Object. The authors adopted the infrafloccular approach for microvascular decompression (MVD) surgery to treat hemifacial spasm (HFS). The inferior portion of the flocculus is retracted to observe the root exit zone of cranial nerve (CN) VII between CN IX and the flocculus. During the procedure, the rhomboid lip, a sheetlike layer of neural tissue forming the lateral recess of the fourth ventricle, is sometimes encountered. The existence of the rhomboid lip in cases of HFS was reviewed to determine the importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The rhomboid lip was observed and correctly incised in 29.1% of cases, which is comparable to previous findings. [7] Including separation of CN IX from the flocculus or choroid plexus, dissection around the lower CNs was necessary in almost half of the cases (45.6%). However, we found no significant relationship with postoperative lower CN palsy.…”
Section: Discussionmentioning
confidence: 99%
“…The rhomboid lip was observed and correctly incised in 29.1% of cases, which is comparable to previous findings. [7] Including separation of CN IX from the flocculus or choroid plexus, dissection around the lower CNs was necessary in almost half of the cases (45.6%). However, we found no significant relationship with postoperative lower CN palsy.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of recognition may be attributed to the inadequate understanding of RL anatomy and structure. In a study conducted by Nakahara et al ( 4 ), only 9 out of 34 patients with HFS had visualized RL during surgery (26.5%), and only 3 cases (8.8%) could be demonstrated on preoperative MRI. On T2WI MRI, a larger RL exhibited high signal cystic manifestations ventral to the flocculus, which connected medially with the fourth ventricle through the foramen of Luschka.…”
Section: Discussionmentioning
confidence: 96%
“…Matsushima et al 19 first reported the concept of MVD for HFS using an infrafloccular approach. They extended the incision in MVD for HFS downward to expose the REZ of facial nerve by dissecting the dorsal arachnoid of the posterior cranial nerve and distracting the flocculus from the side.…”
Section: Discussionmentioning
confidence: 99%
“…This surgical approach for exploring the REZ of the facial nerve from the side is called the infrafloccular approach. 6,19 However, the incision design and the bone window they described are more similar to those in the far lateral approach, which increases the difficulty of exposure and prolongs the operation. Based on the modern concepts of minimally invasive neurosurgery, we gradually improved the operation by combining the surgical concept of the retrosigmoid infrafloccular approach with the advantages of neuroendoscopy.…”
Section: Discussionmentioning
confidence: 99%